The Emerald handbook of tourism economics and sustainable development - Hunjra, Ahmed Imran; Sharma, Anukrati (Building the future of tourism, 2024)
This title in the Building the Future of Tourism series offers a comprehensive overview of the significant challenges faced by the tourism industry in the area of sustainable development. Leading specialists from a range of fields cover a wide spectrum of topics under the main themes of The Economics of Tourism Supply, Tourism Economics at the National, Regional, and Global Level, Tourism Economics and Climate Issues, Economics of Tourism Destination, Socio-cultural Perspective on Sustainable Tourism, and a Futuristic Vision of Tourism Economics. The Emerald Handbook of Tourism Economics and Sustainable Development undertakes both theoretical and empirical research studies using both primary and secondary research methodologies. The issues discussed in this book will be of interest to academics in the tourism and sustainability domains, as well as professionals seeking innovative solutions.